The Role of Integrative Approach for Enhancing Credit Union Sustainability: A Reflection on The Indonesian Credit Union Movement - Stephanus Eri Kusuma; Antonius Sumarwan; Titus Odong Kusumajati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2022)
Most Indonesian credit unions still focus on providing financial services, paying less attention to the roles of credit unions in education, empowerment and flourishing social solidarity of their members. This condition makes credit unions hardly compete with other microfinance providers in Indonesia. While threatening their sustainability prospect, this condition also reduces the capacity of credit unions to empower their members. Inspired by the maximalist approach and the Ledgerwood’s system framework, we suggest an integrative approach for credit union services that is empowered by the optimization of network collaboration.